ปัญหาและอุปสรรคในการทำงานร่วมกันระหว่างหน่วยงานส่วนกลางและส่วนภูมิภาค : กรณีศึกษาการดำเนินงานโครงการป้องกันและลดอุบัติเหตุทางถนนช่วงเทศกาลสำคัญ ของกรมการขนส่งทางบก - พรรณปพร พิลึก (จุฬาลงกรณ์มหาวิทยาลัย, 2022)
This study aims to (1) uncover the obstacles of cooperation between central and provincial agencies of the Department of Land Transport (2) uncover other factors affecting successful working process and (3) propose guidelines for further development of such processes to improve efficiency, using the department’s road accident prevention and reduction efforts during major festivals campaign as the case study. This is a qualitative study, combining document research with information from in-depth semi-structural interviews of fifteen purposively selected samples, based on suitability and the level of involvement in the campaign. This sample group covers personnel from both central and provincial agencies.              The study reveals the problems and obstacles that arise upon the cooperation between central and provincial agencies in the campaign which can be categorized into five main categories which are: (1) communication issues involving central and regional agencies, along with communication channels (2) obstacles arise from unclearness and sluggishness of the commands (3) structural-related obstacles including the limited manpower in each regional body (4) obstacles arise from the policy or the order (5) obstacles arise from the redundancy of the reports on the operation that are required. As the operational factors have been carefully reviewed, it concludes all the affecting factors into five groups which are: organization structure, working procedures, management model, human resources management, and politics. This study proposes recommendations for improving the working efficiency of the Department of Land Transportation which can be enumerated into seven aspects comprising of (1) communication (2) command (3) structure and manpower (4) policy or the order (5) operational support (6) human resources and (7) culture and mindset of the personnel.